Dehydrosilylation of Alcohols Using Gold Nanoparticles Deposited on Citric Acid Modified Fibrillated Cellulose - Suwattananuruk, Butsaratip; Uetake, Yuta; Sakurai, Hidehiro (Synlett, 2024)
The development of an effective catalytic system for the dehydrogenative coupling of hydrosilanes with alcohols remains an ongoing challenge, particularly for alcohol protection applications. In this study, we report the development and optimization of a highly efficient gold catalyst supported on fibrillated cellulose modified with citric acid. The catalyst exhibited remarkable catalytic activity under mild conditions with 0.01–0.05 mol% of Au loading, facilitating the formation of silyl ethers with excellent yield. Notably, our catalytic system overcomes the need for excess alcohol, typically required in such reactions, making it highly practical for alcohol protection applications. This work represents a significant advancement in the field of dehydrosilylation catalysis, offering a sustainable, efficient, and environmentally friendly approach for the synthesis of functional silanol-based materials and alcohol protection applications. The scope of substrates and the utility of the catalyst have been thoroughly studied.
Keywords: gold catalysis; nanoparticles; cellulose; dehydrogenative coupling; hydrosilanes; silylation